Circulating Long Noncoding RNA LIPCAR Predicts Heart Failure Outcomes in Patients Without Chronic Kidney Disease. Issue 4 (April 2019) - Santer, Laura; López, Begoña; Ravassa, Susana; Baer, Christian; Riedel, Isabelle; Chatterjee, Shambhabi; Moreno, María U.; González, Arantxa; Querejeta, Ramón; Pinet, Florence; Thum, Thomas; Díez, Javier
Abstract : The plasma levels of long noncoding RNA LIPCAR are elevated in heart failure (HF) patients with reduced ejection fraction and associated with left ventricular remodeling and poor outcomes. We studied whether the presence of chronic kidney disease (CKD), as defined by an estimated glomerular filtration rate value <60mL/(min·1.73m2) modified the associations of plasma LIPCAR with left ventricular remodeling and outcomes in HF patients. Two hundred and thirty-four patients (mean age 74 [9.14] years, 50% male) were enrolled and followed for 4.73 (0.24–7.25) years. Plasma LIPCAR was detected by real-time quantitative polymerase chain reaction. LIPCAR was increased ( P =0.005) in patients compared with 17 age- and sex-matched controls, directly correlated with age ( P =0.001) and with the maximal early transmitral flow velocity to the mean peak early diastolic velocity of the mitral annulus displacement ratio ( P =0.001) and inversely correlated with estimated glomerular filtration rate ( P <0.001). LIPCAR was associated with hospitalization for HF, cardiovascular death, and a composite of hospitalization for HF or cardiovascular death ( P ⩽0.010), these associations being dependent of estimated glomerular filtration rate. The interactions between estimated glomerular filtration rate and LIPCAR with respect to these outcomes were statistically significant or of borderline significance ( P ⩽0.060). LIPCAR was increased in CKD patients compared with non-CKD patients ( P =0.021). LIPCAR was independently associated with hospitalization for HF ( P ⩽0.039) only in non-CKD patients, but its addition to traditional risk factors did not improve risk prediction in these patients. In conclusion, plasma LIPCAR prognosticates outcomes in elderly HF patients without CKD. Thus, there is an effect modification of CKD on the association of circulating LIPCAR with outcomes in HF patients. Abstract : Supplemental Digital Content is available in the text.